Family Addressing System in the Border Malay Community of Telok Melano : A Review - Dilah, Tuah; Chong, Shin; Yusriadi, -; Hendrikus, Mangku (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study examines the Family Addressing System within the Malay community of Telok Melano, Sarawak, influenced by the Malay culture of Sambas in West Kalimantan. The limited scholarly attention to family addressing systems in this geographical context underscores a critical research gap. The primary objective of this research is to comprehensively document and analyse the practices of family addressing prevalent in Telok Melano. Employing qualitative research methods, particularly in-depth interviews, the study engaged 10 informants—comprising five elderly and five younger individuals from Kampung Telok Melano—to systematically collect data. The analysis draws on theoretical frameworks of bilateral family addressing systems articulated by Millar (1983) and Sorensen (1993), supplemented by comparisons with addressing systems in Sarawak and West Kalimantan. The findings underscore significant parallels with the addressing practices observed in the Malay Sambas community, evidenced by the usage of terms such as 'Pak Long' and 'Mak Long', indicative of the enduring influence of Sambas cultural norms. Furthermore, nuanced distinctions between the family addressing systems in Telok Melano and Kuching, Sarawak were discerned. This study contributes valuable insights into the cultural practices of the Malay community in Telok Melano, serving as a foundational documentation effort particularly relevant amidst socio-cultural transformations following the opening of the Telok Melano-Sematan stretch of the Pan Borneo Highway in 2019.